Pengembangan Media Pembelajaran untuk Meningkatkan Capaian Pembelajaran pada Mata Pelajaran Teknik Dasar Pengelasan - Harsandi, Zaidan Priya; Huda, Khoirul; Kriswanto, Kriswanto; Darsono, Febri Budi; Nuryanta, Muhammad Irfan; Ramadhani, Risky (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to develop and evaluate the feasibility and effectiveness of Android-based learning media in improving students' Learning Outcomes (CP) in Basic Welding Techniques, especially in Gas Metal Arc Welding (GMAW) material at SMKN 3 Salatiga. A quantitative research approach was used with the ADDIE development model and an experimental method using the Pretest-Posttest Control Group Design. The research subjects consisted of two classes, an experimental class and a control class, each consisting of 35 students. Validation by content experts showed a feasibility score of 82%, categorized as very feasible, while validation by media experts produced a score of 74%, categorized as feasible. The results of the normality and homogeneity tests showed that the data were normally distributed and homogeneous. An independent t-test showed a significant difference between the experimental and control groups (p < 0.05) with an average increase of 22.686. In addition, the average N-Gain score in the experimental class was 0.5171 (moderate category), compared to only 0.0199 (low category) in the control class. These findings demonstrate that Android-based learning media has proven effective, feasible, and can be used as an innovative alternative in engineering learning in Vocational High Schools (SMK). This media not only improves student learning outcomes but also supports a more interactive learning process that aligns with current developments in educational technology. This media also has practical benefits in helping teachers deliver material more efficiently and engagingly, and has the potential to support the development of a vocational curriculum that is more adaptive to the needs of the workplace.